ANALISIS STRATEGI DAN EFEKTIVITAS PENGEMBANGAN UKM MELALUI PEMBIAYAAN INVOICE SYARIAH PADA PT. INVESTREE DI MASA PANDEMI COVID-19 - Ningsih, Setia; Yetty, Fitri; Sari, Lili Puspita (DPPM Universitas Pelita Bangsa, 2021)
The development of the SME sector in Indonesia is growing every year. However, since the emergence of the Covid-19 outbreak which has been confirmed for the first time to enter Indonesia since March 2020, the SME sector has become increasingly suboptimal in its development. The presence of fintech makes it easier for people to apply for financing rather than applying for financing to banks. The emergence of fintech companies that have products specifically for SMEs, namely sharia invoice financing such as the one at PT. Investree. The purpose of this study is to determine the strategy and effectiveness of SME development through sharia invoice financing of PT. Investree during the Covid-19 pandemic. This research uses descriptive qualitative research with a case study approach. The result of this research is the strategy implemented by PT. Investree in developing SMEs during the Covid-19 pandemic is to strengthen collaboration with ecosystem partners, improve credit scoring capabilities and innovate business processes. Then, to see the effectiveness of providing financing using indicators of quality, administration, price and the right amount and time which can support the effectiveness of providing sharia invoice financing at PT. Investree during the Covid-19 pandemic.